The Ethics of Stakeholding
VIII, 203 p.
Keywords: The Ethics of Stakeholding brings together leading academics in the fields of political philosophy and social policy to engage with one of the most exciting new paradigms in social policy. Stakeholder policies have been hailed by academics and policy-makers as one of the most promising tools for combating poverty, unemployment and inequality in modern welfare states. This collection by leading academics offers a comprehensive overview of stakeholding and critically explores the ethical foundations of the stakeholder society.